1999
DOI: 10.1089/088922299310809
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of AIDS-Related Primary Central Nervous System Lymphoma with Zidovudine, Ganciclovir, and Interleukin 2

Abstract: AIDS-related primary central nervous system lymphoma (AIDS PCNSL) is a rapidly fatal disease. Conventional therapeutic modalities offer little and new approaches are needed. Previous work has shown that zidovudine (AZT) in combination with other agents is active in retroviral lymphomas. Epstein-Barr virus (EBV) is detected in tumor tissue and cerebrospinal fluid of AIDS PCNSL patients. In a preliminary in vitro study we found that an Epstein-Barr virus-positive B cell line underwent apoptosis on coculture with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 27 publications
0
29
0
3
Order By: Relevance
“…It is interesting to note that like PEL cells, EBV+ cells were also killed by a thymidine analog (AZT) and not by other antiviral nucleosides and that this eect was also inhibited by thymidine. We have recently noted that high dose AZT has marked clinical activity in AIDS related EBV+ primary central nervous system lymphoma (Raez et al, 1999). We recently observed a marked clinical improvement in a PEL patient with lymphomatous meningitis treated with parenteral AZT and IFN-a after having failed conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…It is interesting to note that like PEL cells, EBV+ cells were also killed by a thymidine analog (AZT) and not by other antiviral nucleosides and that this eect was also inhibited by thymidine. We have recently noted that high dose AZT has marked clinical activity in AIDS related EBV+ primary central nervous system lymphoma (Raez et al, 1999). We recently observed a marked clinical improvement in a PEL patient with lymphomatous meningitis treated with parenteral AZT and IFN-a after having failed conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…EBV also seems to be strongly associated with HIV-associated PBL; our series reports the presence of EBV in 74% of published cases. Furthermore, early clinical studies showed promising results using EBV-directed therapy in patients with HIV-associated lymphomas with highdose zidovudine, interleukin 2, and ganciclovir [36,37]. Several investigators have challenged the association between PBL and HHV8.…”
Section: Discussionmentioning
confidence: 99%
“…40 It is tempting to speculate that the presence of both gene products in PTLD might facilitate the selective targeting of actively replicating or reactivated EBV-positive B cells with combination antiviral therapy. 42,43 A more complete characterization of the coexpression of vTK and BGLF-4 gene products in PTLD is likely required before the use of multiple antiviral agents for prophylaxis and/or treatment of PTLD could be broadly advocated.…”
Section: Discussionmentioning
confidence: 99%